Prevalence of COPD in rural population, Muzaffarnagar - Chaturvedi, Rahul; Muzammil, Khursheed; Singh, Nirankar; Davey, Sanjeev; Singh, Jai Veer (Indian Journal of Community Health, 2015)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a life-threatening lung disease that interferes with normal breathing – it is more than a “smoker’s cough”. Recently, Chronic Obstructive Pulmonary Disease (COPD) has gained interest as a major public health concern and is currently the focus of intense research because of its persistently increasing prevalence, mortality, and disease burden in countries of high, middle and low income. Objective: The present study was undertaken with following objectives 1) To asess the prevalence of COPD in 30 years and above in rural catchment of bilaspur which is field practice area of MMC.2) To study the risk factors associated with COPD in a Study population Material and Methods: Study Area: The study was conducted in catchment area of Rural Health Training Center, which is a field practice area of the department of community medicine, Muzaffarnagar Medical college, Muzaffarnagar, having 1323 registered families with population of 1425. Study design: cross-sectional Study period: carried out between 1st April 2014 to 31st March 2015. Results: In the present study, the symptoms of chronic bronchitis were reported by 71 (7.8%) subjects. Out of these only 62 had an airflow limitation based on low FEV1/FVC ratio on spirometry. Conclusion The present study also showed that bidi smoking was more prevalent in the economically underprivileged and those with low educational status due to affordability factor. Bidi smoking was more harmful than cigarette smoking in causation of COPD in the present study. Smoking anytime in life increased the chances of COPD 13 folds